2023
DOI: 10.5472/marumj.1244456
|View full text |Cite
|
Sign up to set email alerts
|

Effect of angiotensin receptor-neprilysin inhibitor treatment on erectile dysfunction in heart failure with a reduced ejection fraction

Abstract: Objective: Erectile dysfunction (ED) is a common condition in patients with heart failure (HF), which impairs quality of life. Our study aimed to compare those patients, who received traditional treatment with a diagnosis of HF and those who received angiotensin receptor-neprilysin inhibitor (ARNI) treatment in addition to the current treatment, in terms of ED at the end of 6 months. Patients and Methods: The study was planned as a single-center, prospective study. The study included 200 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Ceyhun et al also addressed the relationship between ED and NT-pro-BNP in patients with chronic HF and observed a relationship between the increase in NT-pro-BNP and increased severity of ED. Similarly, another study showed that ED was more common in the non-ARNI group that had high NT-pro-BNP levels compared to the ARNI group that had received ARNI for 6 months and had low NT-pro-BNP levels (29,30).…”
Section: Discussionmentioning
confidence: 92%
“…Ceyhun et al also addressed the relationship between ED and NT-pro-BNP in patients with chronic HF and observed a relationship between the increase in NT-pro-BNP and increased severity of ED. Similarly, another study showed that ED was more common in the non-ARNI group that had high NT-pro-BNP levels compared to the ARNI group that had received ARNI for 6 months and had low NT-pro-BNP levels (29,30).…”
Section: Discussionmentioning
confidence: 92%
“…As the elderly male population experiencing menopausal symptoms increases, it is anticipated that there will be a rise in health expenditure and the emergence of various social issues [5,6]. A representative symptom of sexual dysfunction is erectile dysfunction (ED), and a commonly used treatment is using oral type 5 phosphodiesterase (PDE5) inhibitors such as sildenafil [7] and neprilysin (NEP) inhibitor [8]. The activities and functions of the heart and blood vessels are regulated by the interaction between cardiokines and cardiomyokines, which are specific cardiomyocytes-derived peptides [9,10].…”
Section: Introductionmentioning
confidence: 99%